Managing Natural Resources for Sustainable Production Systems: A Research Agenda at the Crossroads? - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
This brief summarizes the outcomes of the SPIA workshop on 'Assessing the Impact of Research on Managing Natural Resources for Sustainable Production Systems’ (https://cas.cgiar.org/spia/events/assessing-impact-research-managing-natural-resources-sustainable-production-systems) and the proposed next steps. Key messages include: